How to Calculate and Measure Solution Concentration using UV-Vis Spectrum Analysis: Supporting Measurement in the Chemical Decomposition, Photocatalysis, Phytoremediation, and Adsorption Process - Asep Bayu Dani Nandiyanto; Risti Ragadhita; Muhammad Aziz (Universitas Pendidikan Indonesia, 2023)
UV-visible (UV-Vis) spectroscopy is a powerful instrument for qualitative investigation and quantitative detection of pollutants in water. UV-Vis spectrophotometry is an analytical method using the concept of transmission of light in UV and Visible wavenumber. Generally, compounds can be identified using UV-Vis Spectrophotometry, based on the concept of light absorption, specifically for compounds with a chromophore group and an auxochrome group. Although the utilization of UV-Vis spectrum analysis has been well-documented, no information regarding detailed step-by-step measurement for examining detailed quantitative analysis, particularly in determining the concentration of an analyte in an aqueous solution sample. Here, this study explores the idea and application of UV-Vis technology in water quality detection, including guidelines for determining the concentration of the sample in an aqueous solution. To support the analysis, we also added practical examples for understanding concentration during the organic decomposition. This paper is intended to be useful for researchers and students in understanding UV-Vis spectrophotometry when analyzing chemical composition during chemical decomposition, photocatalysis, phytoremediation, and adsorption analysis.